Holographic dark energy from the antide Sitter black hole - Ratchaphat Nakarachinda; Chakrit Pongkitivanichkul; Daris Samart; Lunchakorn Tannukij; Pitayuth Wongjun (My University, 2022)
The anti--de Sitter (AdS) black hole plays an important role in the holographic principle. In this study, the upper bound in energy corresponding to the mass of the Schwarzschild black hole is modified to be that of the AdS black hole. Via the correspondence between the ultraviolet and infrared cutoffs, the constant term in the energy density of the holographic dark energy can be obtained from the negative cosmological constant from the black hole. Interestingly, the proposed dark energy model could drive the late-time expansion of the Universe without the causality violation. The cosmic evolution is investigated by choosing the Hubble and particle horizons as the IR length scales. It is found that the accelerated expansion at late time can be obtained for both cases. The likelihood analysis on the model parameters is also performed. This result may shed light on the connection between the AdS black hole and the de Sitter (dS) spacetime in the context of cosmology.
Keywords: Black hole (networking); Cosmological constant; Black Holes and Theoretical Physics